Determination of Microbial Susceptibility to Sulfanilamides by Electrooptic Analysis - O. I. Guliy; V. D. Bunin; O. S. Larionova; E. G. Potemkina; O. V. Ignatov (Антибиотики и Химиотерапия)
The effect of sulfanilamides (soluble streptocid as an example) on changing of the electrophysical properties (EP) of microbial cells of Escherichia coli XL-1, BL-Ril, Pseudomonas putida C-11 and BA-11 was studied. It was shown that significant changes in the orientation spectra (OS) of the cell suspensions incubated at various concentrations of the sulfanilamide resulted in changing of the electrooptic (EO) signal of the cell suspension at the first five frequencies of the orientation electric field (10-1000 Hz) with the use of soluble streptocid in a concentration of 0.3 mcg/ml. The dynamics of the drug effect on the microbial cells demonstrated a decrease of the EO signal value 5 minutes after the exposure by ~59% vs. the control (the cells not exposed to the drug). During the following exposure the EO signal value practically did not change (within 5%). The changes of the OS of the cell suspensions exposed to soluble streptocid significantly differed for the susceptible and resistant strains. Determination of the activity of sulfanilamides by electrooptic analysis of microbial cell suspensions was considered possible. Changing of the microbial suspencion OS under the effect of sulfanilamides can be used as a test on the microbial cell susceptibility to drugs.